Congenital anomaly of coronary artery: absence of left circumflex artery - Rawala, Muhammad Shabbir (J Community Hosp Intern Med Perspect, 2019)
The prevalence of congenital coronary artery anomalies is approximately 1% in the general population. They are a common cause of sudden death in younger persons. Congenital absence of the left circumflex artery is usually a benign condition but can cause symptoms of exertional angina. We present a case of a 59-year-old female who presented with complaints of chest pain. She was evaluated by the cardiology service. An invasive angiogram identified the absence of the circumflex artery, a large right coronary artery, and large septal and diagonal branches of the left main coronary artery possibly as a compensatory mechanism to supply blood to the LCx territories. It is important to define coronary anatomy as anomalies dictate which cardiac intervention should be attempted in cases of ischemia.